Origin of Suppression of Proximity‐Induced Superconductivity in Bi/Bi2Sr2CaCu2O8+δ Heterostructures. Issue 9 (9th August 2020) - Kundu, Asish K.; Wu, Ze‐Bin; Drozdov, Ilya; Gu, Genda; Valla, Tonica
Abstract: Mixing of topological states with superconductivity could result in topological superconductivity with the elusive Majorana fermions potentially applicable in fault‐tolerant quantum computing. One possible candidate considered for realization of topological superconductivity is thin bismuth films on Bi2 Sr2 CaCu2 O 8 + δ (Bi2212). Here, angle‐resolved and core‐level photoemission spectroscopy studies of thin Bi films grown in‐situ on as‐grown Bi2212 showing the absence of proximity effect are presented. It is found that the electron transfer from the film to the substrate and the resulting severe underdoping of Bi2212 at the interface is a likely origin for the absence of proximity effect. A possible way of preventing a total loss of proximity effect in this system is also proposed. These results offer a better and more universal understanding of the film/cuprate interface and resolve many issues related to the proximity effect. Abstract : Ability of cuprate superconductors to induce superconductivity in layers grown on them is still an open question. Here, it is found that the interfaces between metallic films and cuprate superconductors become heavily underdoped due to the electron transfer from the film. This results in suppression of superconductivity at the interface and prevents the proximity effect in heterostructures involving cuprates.